TINDAK TUTUR EKSPRESIF PADA VIDEO WATCH DI MEDIA SOSIAL FACEBOOK - Vitaloka, Widya; Djumingin, Sulastriningsih; Hasriani, Hasriani (Universitas Negeri Makassar, 2024)
This research aims to describe the form and function of expressive speech acts in Watch videos on Facebook social media. This type of research is qualitative research. Data collection in this research uses listening and note-taking techniques. The results revealed that the form of speech acts on Watch videos on Facebook are literal direct speech acts, literal indirect speech acts, non-literal direct speech acts and non-literal indirect speech acts. The functions of expressive speech acts used in Watch videos on Facebook social media are criticising, blaming, praising, thanking, apologising, congratulating, and condoling. The use of various expressive speech act functions in Watch videos on Facebook is used to express the speaker's feelings. The function of criticising, blaming is intended as a form of dislike for something. The function of praising, thanking, congratulating and expressing condolences is intended as a form of good response from the speaker to what is seen, heard or felt. While the function of apologising is intended as a sense of regret of the speaker for what he did, the function of apologising speech is mostly spoken by women and men as a form of regret for the mistakes made.